Analisis Implementasi Kebijakan Undang-Undang Nomor 7 Tahun 2021 tentang Harmonisasi Peraturan Perpajakan dalam Rangka Meningkatkan Penerimaan Pajak Pertambahan Nilai di KPP Madya Dua Jakarta Timur - Verry Irawan; Nur Hidayat (Jurnal Pajak Vokasi (JUPASI), 2026)
The COVID-19 pandemic significantly impacted Indonesia’s economy, particularly in decreasing state revenue from taxation. In response, the government enacted Law Number 7 of 2021 concerning the Harmonization of Tax Regulations (UU HPP), which includes adjustments to the Value Added Tax (VAT) rate. This study aims to analyze the implementation of the VAT policy under the UU HPP in efforts to increase state revenue, specifically at the Tax Office (KPP) Madya Dua Jakarta Timur. A qualitative approach was employed using data collection techniques such as interviews, documentation, and observation, analyzed through Grindle’s policy implementation theory. The results indicate that the implementation of the VAT policy still faces challenges, including resistance from taxpayers, limited understanding of regulatory changes, and concerns over price increases due to the VAT rate hike. However, efforts by KPP Madya Dua Jakarta Timur, such as public outreach, enhanced digital services, and improved monitoring, have helped mitigate implementation barriers. The VAT policy is expected to support economic recovery while encouraging sustainable taxpayer compliance and contribution. Keywords: Law No. 7 of 2021 (HPP Law); Value Added Tax (VAT); Policy Implementation; State Revenue; KPP Madya Dua Jakarta Timur